The influence of quarternary salt on hyaluronan conformation and particle size in solution - Gřundělová, Lenka; Mráček, Aleš; Kašpárková, Věra; Minařík, Antonín; Smolka, Petr (Carbohydrate polymers, 2013)
Interaction of hyaluronan (NaHy) with the quaternary salt, benzalkonium chloride (BAC), was studied. Based on the DLS experiments, viscometry and surface tension measurements executed on hyaluronan samples with two molecular weights of Mw=1.8 MDa and Mw=0.35 MDa, the hypothesis was proposed suggesting that at certain BAC concentrations, hyaluronan can form aggregates, which lead to increase of the polymer coil size measured as z-average diameter. Moreover, it was confirmed that within the whole range of BAC concentrations, repeated variations in size and conformations of polymer coils occur, being connected with the critical micellar concentration of BAC and with hydrophobic interactions of non-polar segments of BAC with hyaluronan hydrophobic domains. Tensiometry, DLS and viscometry data support the assumption that variations of thermodynamical "favourability" of BAC-BAC or NaHy-BAC interactions take place in hyaluronan solutions, based on the BAC concentration.
Keywords: micely; Salts; roztoky; Hyaluronan conformation; Solutions; soli; benzalkoniové sloučeniny; Carbohydrate Conformation; Micelles; Hyaluronan; velikost částic; Quarternary salts; Critical micellar concentration; Surface Tension; Benzalkonium Compounds; Hyaluronan hydrophobic interactions; kyselina hyaluronová; Dynamic light scattering; povrchové napětí; konformace sacharidů; Hyaluronic Acid; Particle Size